LA EXPOSICIÓN DE ARTE VISUAL NOVELADA POR ENRIQUE VILA-MATAS - SIMION, Sorina Dora (Studia Universitatis Babeș-Bolyai Philologia, 2021)
The Art Exhibition as a Novel by Enrique Vila-Matas. I set out to analyze, using the New Rhetoric methods, the book entitled Cabinet d`amateur, an oblique novel published by the contemporary Spanish writer Enrique Vila-Matas in 2019, at the same time as the opening of an exhibition whose curator he was in the Whitechapel Gallery in east London. Choosing the six visual art works, different in nature, concept, and aesthetics, from the collection of the “laCaixa” Foundation represents an occasion for the writer, led by curiosity, to investigate the works of art and to make a personal, purely subjective selection, on which he reflects in his heterogenic work as a genre: the catalogue of an exhibition, memoirs, essay (auto)biography, the skeleton of an oblique novel of the future. The selected works of art (I.G., the mysterious portrait of a woman by the painter Gerhard Richter; an installation, Petite, by Dominique Gonzalez-Foerster; a videoclip, La lección respiratoria, belonging to the artist Dora García; Milonga, Carlos Pazos’s self-portrait; a detailed scenery, Une poignée de terre, by Miquel Barceló and a photography of Theban by Andreas Gursky, in an overlap of an aerial view with one detailed figure) are included in the text as a starting point for meditations and reflections upon the nature of the art in general, because the metaphor of the literary work, the novel of the future, is precisely the building of Rem Koolhass, the library in Seattle, in which different styles overlap and whose shapes are imprecise, undetermined, incongruent, disharmonic and lacking in logic. Literature, visual arts, music, and architecture are associated, and different figures are used to point out the aesthetic of the negative and the idea that form and content are interchangeable. REZUMAT. Expoziția de artă vizuală ca roman al lui Enrique Vila-Matas. În această lucrare, ne propunem să analizăm, apelând la metodele neoretoricii, cartea publicată de scriitorul contemporan spaniol Enrique Vila-Matas, în 2019, cu titlul Cabinet d`amateur, una novela oblicua (Cabinet d`amateur, an oblique novel) odată cu vernisajul expoziției de la Whitechapel Gallery din estul Londrei al cărei curator a fost. Alegerea celor șase opere de artă vizuală, diferite ca natură, concept și estetică, din colecția Fundației „laCaixa” este un prilej pentru scriitor de a cerceta, mânat de curiozitate, operele și de a face o selecție personală, pur subiectivă, asupra căreia reflectează în opera sa eterogenă ca gen: catalog al unei expoziții, memorii, eseu, (auto)biografie literară, schelet al unui roman oblic al viitorului. Operele selectate (I.G., un portret misterios de femeie al pictorului Gerhard Richter; o instalație, Petite, de Dominique Gonzalez-Foerster; un video, La lección respiratoria, aparținând artistei Dora García; Milonga, autoportretul lui Carlos Pazos; un peisaj în detaliu, Une poignée de terre, de Miquel Barceló și o fotografie a Tebei de Andreas Gursky, într-o suprapunere a unei vederi aeriene cu una figurativă detaliată) sunt incluse în text ca puncte de plecare pentru meditații și reflecții asupra naturii artei în general, deoarece metafora arhitecturii operei literare, romanul viitorului, este chiar clădirea lui Rem Koolhass, biblioteca din Seattle, în care se suprapun stiluri diferite și ale cărei forme sunt imprecise, neterminate, incongruente, dizarmonice și lipsite de logică. Sunt asociate literatura, artele vizuale, muzica, arhitectura, se recurge la figuri diferite pentru a evidenția estetica negativului și ideea că forma și conținutul sunt substituibile. Cuvinte-cheie: Enrique Vila-Matas, Cabinet d´amateur, una novela oblicua, analiză retorico-generală, expoziția ca roman, biografie literară